A lightweight multifunctional interlayer of sulfur–nitrogen dual-doped graphene for ultrafast, long-life lithium–sulfur batteries. Issue 40 (23rd September 2016) - Wang, Lu; Yang, Zhi; Nie, Huagui; Gu, Cancan; Hua, Wuxing; Xu, Xiangju; Chen, Xi'an; Chen, Ying; Huang, Shaoming
Abstract : A lightweight multifunctional SNGE interlayer was developed, which enabled the PCNT–S cathode to deliver a high reversible specific capacity and extraordinarily excellent cycling stability at ultrahigh rates. Abstract : Lithium–sulfur batteries are a promising candidate for next-generation battery systems owing to their low cost and high theoretical capacity and energy density. However, the notorious shuttle effect of the intermediate polysulfides as well as low conductivity of sulfur greatly limits their practical applications. Here, we introduce a new design that uses a porous-CNT/S cathode (PCNT–S) coupled with a lightweight multifunctional porous sulfur–nitrogen dual-doped graphene (SNGE) interlayer. It is confirmed that the introduced SNGE has outstanding conductivity, high ability to trap polysulfides, ability to modulate Li2 S2 /Li2 S growth, and the functionality to protect separator integrity. With such rich functionalities, the SNGE interlayer enables the PCNT–S cathode to deliver a reversible specific capacity of ∼1460 mA h g −1 at 0.25C and a much higher rate performance, up to 40C, with a capacity retention of 130 mA h g −1 . Critically, these cathodes exhibited ultrahigh cyclability when cycled at 8C for 1000 cycles, exhibiting a capacity degradation rate of 0.01% per cycle. To the best of our knowledge, such a low capacity degradation rate beyond 5C in the cathodes of advanced Li–S batteries has been reported only rarely. These results impressively revealed the outstanding high-power output performance of the Li–S batteries.